Educational Policy in Ceará: strategic processes - Sofia Lerche Vieira; David Nathan Plank; Eloisa Maia Vidal (Universidade Federal do Rio Grande do Sul, 2019)
The article discusses strategic processes for the formulation and implementation of educational policy in Ceará, Brazil in the period 1995-2015, based on the theories of governance and path dependence. The text analyzes aspects related to the state fiscal balance, meritocratic recruitment practices and monitoring mechanisms associated with management by results. In this scenario, three strategic processes were instrumental in creating favorable conditions for improving education: collaboration, mobilization and accountability. Evidence is presented that such processes, historically constructed in Ceará education, paved the way for the institution of a favorable institutional culture for change, such as the improvement of the results obtained by the state in external evaluation processes.